Feasibility and Efficacy of Percutaneously Delivered Leadless Cardiac Pacing in an In Vivo Ovine Model. (5th December 2014) - KORUTH, JACOB S.; RIPPY, MARIAN K.; KHAIRKHAHAN, ALEXANDER; LIGON, DAVID A.; HUBBARD, CHRISTOPHER A.; GOAR, FREDERICK ST.; LEE, RANDALL; RIBEIRO, LEONARDO; MILLER, MARC; DUKKIPATI, SRINIVAS; NEUZIL, PETR; REDDY, VIVEK Y.
Preclinical Feasibility of a Leadless Pacemaker Introduction In this in vivo ovine study, we describe the course of pacing and sensing parameters during follow‐up as well as the gross and histopathological features at the implant site of the recently described leadless cardiac pacemaker (LCP). Methods and Results All sheep underwent LCP implantation in the right ventricular (RV) apex. Serial pacing/sensing thresholds were assessed. In the first cohort, 11 animals were followed up for a period of 3 months, followed by necropsy. In the second cohort, 7 additional sheep were followed for a period of up to 18 months. Mean pacing and sensing thresholds in the 3‐month cohort were 1.0 ± 0.5 V and 9.0 ± 3.7 mV at implant, and 0.7 ± 0.2 V and 8.1 ± 3.9 mV at 90 days, respectively. At necropsy at 3 months, all devices were securely implanted at the RV apex without extrusion of helix beyond the RV wall. Besides endocardial reactive changes in the RV apex surrounding the distal portion of the LCP, there were no other grossly visible abnormalities. In the second cohort (7 sheep), mean pacing and sensing thresholds were 1.0 ± 0.5 V and 9.9 ± 3.8 mV at implant, and 0.86 ± 0.4 V and 4.25 ± 1 mV, respectively, at 18 months of follow‐up. Conclusion We demonstrate that after implantation of the LCP, pacing/sensing parameters remain adequate up to 18 months in follow‐up. In addition, pathological changes at the implant site and within the RV are limited in severity at 90 days, supporting the efficacy and safety of this novel approach to pacing.